Are unsolicited ratings biased? Evidence from long-run stock performance - Byoun, Soku; Fulkerson, Jon A.; Han, Seung Hun; Shin, Yoon S. (Journal of Banking & Finance, 2014)
We test the biasedness of unsolicited ratings relative to solicited ratings using the ex post firm performance measured by the long-run stock performance of firms following rating announcements and changes. We find that the announcements of new unsolicited ratings are followed by negative long-run stock performance, while those of new solicited ratings are followed by insignificant long-run stock performance. These results are inconsistent with the conservatism hypothesis that suggests that unsolicited ratings are downward biased. We further demonstrate that firms with solicited upgraded (downgraded) ratings experience subsequent positive (negative) abnormal stock performance, while those with unsolicited rating changes have zero abnormal stock performance. The differential stock performance following rating changes between solicited and unsolicited ratings reflect the differential information carried by each type of rating rather than the biasedness in ratings. Specifically, while solicited ratings are based on both public and private information, unsolicited ratings are mainly based on public information. Overall, we find no evidence for a downward bias in unsolicited ratings.